Platinum accumulation in oxaliplatin‐induced peripheral neuropathy - Wei, Guoli (J Peripher Nerv Syst, 2021)
Oxaliplatin‐induced peripheral neuropathy (OIPN) is a common and dose‐limiting toxic effect that markedly limits the use of oxaliplatin and affects the quality of life. Although it is common, the underlying mechanisms of OIPN remain ambiguous. Recent studies have shown that the platinum accumulation in peripheral nervous system, especially in dorsal root ganglion, is a significant mechanism of OIPN. Several specific transporters, including organic cation transporters, high‐affinity copper uptake protein1 (CTR1), ATPase copper transporting alpha (ATP7A) and multidrug and toxin extrusion protein 1 (MATE1), could be associated with this mechanism. This review summarizes the current research progress about the relationship between platinum accumulation and OIPN, as well as suggests trend for the future research.